Diamond Seed Size and the Impact on Chemical Vapor Deposition Diamond Thin Film Properties. (3rd June 2020) - Bai, T.; Wang, Y.; Feygelson, T. I.; Tadjer, M. J.; Hobart, K. D.; Hines, N. J.; Yates, L.; Graham, S.; Anaya, J.; Kuball, M.; Goorsky, M. S.
Abstract : Diamond seeds were assessed for their role in the heterogeneous nucleation for diamond films deposited on silicon using chemical vapor deposition. Two diamond seed sizes—4 nm and 20 nm—were studied. The study revealed that the larger seed size, even when with a smaller seed density, produces a larger grain size near the interface region, and led to a higher in-plane thermal conductivity as measured by Raman thermography. By fine control of the seed size and density, thermal conductivity near the nucleation region can therefore be improved. This demonstrates that the seeding condition is critical to diamond film growth for thermal applications in electronic devices.